Synthesis and characterization of bidentate ligands with ruthenium complex for luminescent testing - Khaw, Ying Ying. (Universiti Malaysia Sarawak (UNIMAS), 2016)
a—Diimine such as diazabutadiene was a type of bidentate Schiff base ligand used for the synthesis of ruthenium complex as it mimicked the aromatic bipyridine ruthenium complex that emits luminescence. Many diimine ligands structures had been modified to increase the emission quantum yield and luminescence lifetime. DAB-containing complexes had been widely studied while BIAN compound itself had only been recently explored for the photophysical properties due to its electron delocalization from the naphthalene unit. Their unique properties allowed further research on the binding to metal especially ruthenium(ll) complex to test on the luminescence properties. Thus, the objective of this project was to synthesize and characterize the ct—diimine ruthenium(ll) complex for luminescent testing. In this study, the ligands were synthesized by using a diketone and substituted aniline through condensation process. The ruthenium(ll) complexes containing phosphorus type ligands were synthesized by the substitution of DAB into RuC13•xH20 while BIAN substituents into under reflux condition in ethyl acetate and dichloromethane respectively. The complexes were confirmed to have binding with the diimine and P-containing ligands in an octahedral geometry. Ruthenium(ll) complex with CH3-BIAN ligand was found to produce luminescence under UV lamp.